The insufficiency fracture of the sacrum - Hatzl-Griesenhofer, M.; Pichler, R.; Huber, H.; Maschek, W. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: The insufficiency fracture of the sacrum is often radiographically occult. Bone scintigraphy is a method of reference for the diagnosis; the results have been analysed retrospectively. Methods: Bone scintigraphy was done on patients who, predominantly after minor trauma, suffered from lower back pciin and whose radiographic findings were negative. Results: During a 24 month period, a sacral insufficiency fracture was diagnosed in 102 patients. H-shaped hyperfixation of the tracer - described as typical - was present in only 19.6% of the cases. Tracer accumulation was found as follows: located uni/bilateral in the sacral wings (32.4%/6.9%), horizontal (27.4%) and half H-shaped (13.7%). In 85% of the cases there were further fractures with main localisations in the pubic bone, in the spine and the ribs. Conclusion: The insufficiency fracture of the sacrum as cause of lower back pain is not uncommon, especially in postmenopausal women with risk factors. Bone scintigraphy is not only an adequate procedure for the detection of often radio-graphically occult sacral fractures, but also an easy method to reveal the often concomitand fractures.
Keywords: Bone scintigraphy; spontaneous fracture; occult fracture; insufficiency fracture; osteoporosis; sacrum